Metabolic Influences of Vitamin D and Calcium Deficiency on Oral Health among Libyan Pregnant and Non-Pregnant Women - Emni Elshaali; Samira Abdulrahman; Mahadia Abdalrahman (AlQalam Journal of Medical and Applied Sciences, 2025)
There have been physiological changes, fluctuations in hormones, and higher nutrient demands, all recognized as risk factors for periodontal disease and dental caries. There is a wealth of literature linking well-established roles of vitamin D and calcium in oral health. These nutrients frequently show a deficiency among women during pregnancy. This investigation aimed to assess the oral health condition along with the levels of calcium and vitamin D in both expectant and non-expectant women. A total of four hundred thirty women participated in the study, but 80 females dropped out of further analysis. Of the remaining 350 women, 175 were pregnant women and 175 were non-pregnant women who agreed to participate using a comparative, cross-sectional study design. Data collection included oral health clinical evaluations using the DMFT index, along with the use of questionnaires regarding nutrition, oral hygiene practices, and vitamin supplement use. This researcher revealed that the rate of dental caries was higher in pregnant women at 60.0 %, compared to 42.9 % (p < 0.001) in non-pregnant women. In addition, they found a substantial difference in the proportion of pregnant women taking supplements who achieved sufficient vitamin D status, with 80.0 % compared to 57.1 % (p < 0.001). Additionally, pregnant women had lower average vitamin D and calcium levels when compared to the non-pregnant group respectively (vitamin D 19. 8 ± 5. 0 ng/mL compared to 28. 2 ± 5. 8 ng/mL, p < 0. 001; calcium 7. 8 ± 0. 5 mg/dL, verse 9. 2 ± 0. 4 mg/dL, p < 0.001). There was an inverse relationship between DMFT and blood status of vitamin D (r = -0.52, *p* = 0.001) and calcium (r = -0.68, p = 0.001) in pregnant women. This research study illustrated an association between pregnancy, bad oral health, and low vitamin D and calcium status, although they used considerable numbers of supplements. Data suggested that improved dietary advice offered to women during pregnancy is likely to improve the oral health status of pregnant women and their infants.